البعد النفطي لسياسات الولايات المتحدة الأمريكية في دول الخليج العربي - اسماعيل, عصام; سويد, عمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يؤكد هذا البحث على الأهمية الكبيرة للنفط وتأثيره على العلاقات الدولية على الصعيدين السياسي والاقتصادي، وهو ما يدفع الدول الكبرى وعلى رأسها الولايات المتحدة الأمريكية لتأمين الإمدادات النفطية اللازمة لها بشكل دائم وبأي طريقة ممكنة، ويهدف البحث للتعريف بأهم مرتكزات السياسة الأمريكية النفطية وأهمية حماية الحزام الأمني النفطي على الصعيد العالمي بشكل عام والخليجي بشكل خاص، وتطور الوسائل التي تتبعها الولايات المتحدة للسيطرة على النفط الخليجي واستغلاله إلى أبعد حد ممكن، سواءً من خلال توقيع اتفاقيات الاحتكار وحتى الوصول إلى إتباع سياسة شن الحروب وافتعال الأزمات، كما يشير البحث إلى التاريخ السياسي والاقتصادي للاستغلال الأمريكي للنفط الخليجي بالرغم من الاعتقاد السائد بأن الولايات المتحدة هي حليف استراتيجي لدول الخليج. وتوصل البحث إلى العديد من النتائج، وقدم بعض التوصيات. This research confirms the great importance of oil and its impact on international relations at the political and economic levels, which drives the major countries, especially the United States of America, to secure the necessary oil supplies permanently and in any way possible. The research aims to introduce the most important pillars of US oil policy and the importance of protecting the oil security belt In general and the Gulf in particular, and the development of the means followed by the United States to control and exploit the Gulf oil as far as possible, both through the signing of the agreements of monopoly and even access to the policy of waging wars or making crises, as research refers to the political and economic history of the American exploitation of the Gulf oil despite the prevailing belief that the United States is a strategic ally of the Gulf states. The research founded many results and made some recommendations.